2021
DOI: 10.1101/2021.12.23.21268244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of casirivimab and imdevimab, and sotrovimab during Delta variant surge: a prospective cohort study and comparative effectiveness randomized trial

Abstract: IMPORTANCE The effectiveness of monoclonal antibodies (mAbs), casirivimab and imdevimab, and sotrovimab, for patients with mild to moderate Covid-19 from the Delta variant is unknown. OBJECTIVE To evaluate the effectiveness of mAbs for the Delta variant compared to no treatment, and the comparative effectiveness between mAbs. DESIGN, SETTING, AND PARTICIPANTS Two parallel studies among patients who met Emergency Use Authorization criteria for mAbs from July 14, 2021 to September 29, 2021: i.) prospective obs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 5 publications
2
20
0
Order By: Relevance
“… 24 Even more, for patients with mild to moderate COVID‐19 from the Delta variant, a propensity matched models also demonstrated that neutralizing mABs treatment using casirivimab and imdevimab, or sotrovimab was associated with reduced risk of hospitalization or death compared to no treatment (RR: 0.40; 95% CI: 0.28–0.57). 25 In contrast to the recent meta‐analysis of four studies investigating the individual effect of each neutralizing mABs for nonhospitalized patients, no consistent results were found in each comparison. 27 The present meta‐analysis including five RCTs and conducting the overall effect based on the pooled analysis of all included studies demonstrated the benefit of adding neutralizing mABs for nonhospitalized patients.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“… 24 Even more, for patients with mild to moderate COVID‐19 from the Delta variant, a propensity matched models also demonstrated that neutralizing mABs treatment using casirivimab and imdevimab, or sotrovimab was associated with reduced risk of hospitalization or death compared to no treatment (RR: 0.40; 95% CI: 0.28–0.57). 25 In contrast to the recent meta‐analysis of four studies investigating the individual effect of each neutralizing mABs for nonhospitalized patients, no consistent results were found in each comparison. 27 The present meta‐analysis including five RCTs and conducting the overall effect based on the pooled analysis of all included studies demonstrated the benefit of adding neutralizing mABs for nonhospitalized patients.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the mortality rate was lower in the neutralizing mAB group than in the control group (0% vs. 3.5%, p = 0.02) 24 . Even more, for patients with mild to moderate COVID‐19 from the Delta variant, a propensity matched models also demonstrated that neutralizing mABs treatment using casirivimab and imdevimab, or sotrovimab was associated with reduced risk of hospitalization or death compared to no treatment (RR: 0.40; 95% CI: 0.28–0.57) 25 . In contrast to the recent meta‐analysis of four studies investigating the individual effect of each neutralizing mABs for nonhospitalized patients, no consistent results were found in each comparison 27 .…”
Section: Discussionmentioning
confidence: 96%
“…In a prospective, propensity-matched observational cohort study in non-hospitalized patients with mild to moderate COVID-19 due to Delta variant (n = 3069), casirivimab plus imdevimab or sotrovimab treatment significantly reduced the risk of hospitalization or death by 28 days compared with no treatment (risk ratio 0.4; 95% CI 0.28-0.57), with the comparative effectiveness between the treatments appearing to be similar [39]. In addition, in an ongoing randomized, parallel-assignment, open-label phase III OPTIMISE-C19 trial (NCT04790786) in patients with COVID-19 who received casirivimab plus imdevimab (n = 2454) or sotrovimab (n = 1104), the median hospital-free days were 28 days [39].…”
Section: Features and Properties Of Sotrovimabmentioning
confidence: 99%
“…In addition to RCT, data from observational cohorts ( 8 11 )have also confirmed the effectiveness of mAbs, but comparative analysis between different options available are lacking ( 12 , 13 ). Considering the rapid epidemiological evolution, with the emergence of new Variants of Concern (VoCs) ( 14 16 ) that have been shown to escape ( 17 ) the action of mAbs in vitro ( 18 , 19 ) and in vivo ( 20 ), real-life data about clinical impact and mAb comparison are useful to better clarify the scenario of currently existing drugs.…”
Section: Introductionmentioning
confidence: 99%